Studies on the Impact of Thermal Stress on Survival and Development of Adaptive Thermotolerance in Immature Stages of Anopheles culicifacies - V. Swain, K. Raghavendra, T.K. Barik, (Journal of Ecobiotechnology, 2010)
Background & objectives: Not much is known about the impact of temperature on the survival of a number of important vector species of mosquitoes. Most survival analyses of mosquitoes are reported in adults and not in immature stages. Impact of thermal stress and development of adaptive thermotolerance in late third instar larvae of An. culicifacies was evaluated in the laboratory. Methods: Late third instar larvae were exposed to temperatures of 37°C, 39°C, 41°C, 43°C and 45°C and lethal time to cause 50% mortality (LTM50), LTM90 values were calculated. To assess the adaptive thermotolerance, larvae were exposed to 37°C and 39°C and these thermally pre-adapted larvae were later re-exposed to higher temperature of 43ËšC and 45ËšC. Results: All larvae survived at 37°C up to 360 minutes whereas at 45°C they succumbed within 60 minutes of exposure. Larvae pre-adapted at 37°C and 39°C were re-exposed to 43°C and 45°C and larvae pre-adapted at 39°C were more thermo-tolerant than larvae pre-adapted at 37°C which depended on exposure time. Interpretation & Conclusions: Pre-adapted larvae derived from higher temperature were more thermotolerant than the larvae pre-adapted at lower temperature. This preliminary study on the impact of temperature on thermotolerance of larvae of An. culicifacies has highlighted the importance of the studies on the interaction of abiotic factors specially temperature on the survival of disease vectors. --- 1National Institute of Malaria Research, Sector-8, Dwarka, New Delhi-110077 2Department of Zoology, K.N.W. College, Bhubaneswar, Orissa-751001 --- Please Cite This Article As: K. Raghavendra, T.K. Barik, V. Swain. 2010. Studies on the Impact of Thermal Stress on Survival and Development of Adaptive Thermotolerance in Immature Stages of Anopheles culicifacies. J. Ecobiotechnol. 2(5):25-30.